2013
DOI: 10.1016/j.solener.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of methylene blue under visible light using PVP-capped ZnS and CdS nanoparticles

Abstract: Photocatalysis based on semiconductor quantum dots which utilize the solar energy can be used for the elimination of pollutants from aqueous media and applied for water purification. Degradation of dyes is a standard method to check the photocatalytic activity of any type of photocatalyst. In this paper polyvinyl pyrrolidone (PVP)-capped ZnS and CdS nanoparticles were prepared by a simple microwave irradiation method and studied in detail for their photocatalytic activity in visible range. The obtained nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 26 publications
(27 reference statements)
5
41
0
1
Order By: Relevance
“…The studies on Pourahmad [5] observed the degradation rate of 41% when it was interacted with Ag 2 S (without MCM-41) at the irradiation time of 60 min. According to Soltani et al [18] PVP-capped ZnS and CdS showed the degradation efficiencies of 31% and 65% after 360 min of exposure, respectively. In another study, Soltani et al [19] reported that CdS, PVP capped CdS, ZnS/CdS and CdS/ZnS degraded methylene blue to its half, after 210, 60, 120 and 90 min of irradiation time, respectively.…”
Section: Photocatalytic Propertymentioning
confidence: 97%
“…The studies on Pourahmad [5] observed the degradation rate of 41% when it was interacted with Ag 2 S (without MCM-41) at the irradiation time of 60 min. According to Soltani et al [18] PVP-capped ZnS and CdS showed the degradation efficiencies of 31% and 65% after 360 min of exposure, respectively. In another study, Soltani et al [19] reported that CdS, PVP capped CdS, ZnS/CdS and CdS/ZnS degraded methylene blue to its half, after 210, 60, 120 and 90 min of irradiation time, respectively.…”
Section: Photocatalytic Propertymentioning
confidence: 97%
“…where d is the optical path length when the light transmit through a cuvette and A is the absorbance determined from UV-vis spectra [55]. By extrapolating the linear region of the curve to the energy axis for zero absorption coefficient, the optical bandgap energy of the ZnO nanospikes and commercial ZnO nanoparticles is estimated to be 3.1 eV and 3.2 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Beer-Lambert law, the concentration of CR is proportional to the absorbance of CR, so the photocatalytic activity (PA), also known as the degradation efficiency (R or R%), can be calculated by [26,29]:…”
Section: Catalytic Properties Of Cds Nanopowdersmentioning
confidence: 99%
“…Furthermore, CdS nanoparticles easily aggregate in aqueous solution during the preparation process, which accordingly results in rather lower efficiency [1]. Thus, they are a few reasons for the fabrication of the capped CdS particles [25,26], in which the capping agent has at least two rolesto prevent the aggregation of particles and to make passive the reactive surface. In fact, the influence of capping agents on catalytic properties of nanoparticles is disputable -while the capping agents usually act as a physical barrier to restrict the free access of reactants to catalytic nanoparticles, they can also be utilized to promote the catalytic performance of nanocrystals [27].…”
Section: Introductionmentioning
confidence: 99%